Crop Rotation and Management Effect on Fusarium spp. Populations. Issue 1 (1st January 2015) - Marburger, David A.; Venkateshwaran, Muthusubramanian; Conley, Shawn P.; Esker, Paul D.; Lauer, Joseph G.; Ané, Jean‐Michel
ABSTRACT: Fusarium spp. are common fungal pathogens that infect a number of field and vegetable crops. Crop rotation, genetic resistance, and fungicides are the primary methods used for managing these pathogens; however, there is a lack of information regarding the interactions between these management strategies and how they impact Fusarium spp. population dynamics. Therefore, the objective of this research was to quantify the effect of crop rotation and management (i.e., variety selection and fungicide use) on F. graminearum, F. oxysporum, and F. virguliforme populations in the soil using real‐time quantitative polymerase chain reaction (qPCR). Soil samples were collected in 2011 and 2012 from a long‐term corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.]–wheat ( Triticum aestivum L.) rotation study near Arlington, WI, and populations for each species (spores g −1 of soil) were quantified from extracted soil DNA. Fusarium oxysporum was the most prevalent Fusarium sp. found. Crop rotation and management did not impact F. oxysporum populations nor F. virguliforme presence. A crop rotation by fungicide interaction was found for F. graminearum ( P < 0.001), but this interaction was primarily affected by crop rotation. As expected, F. graminearum was found more often in plots with wheat as part of the rotation. This study found few interactions among crop rotation, variety selection, and fungicide use for controlling populations of three Fusarium spp. in the soil, and significant interactions or individual control methods were dependent on the species being examined.